MEDIA KOMIK CERITA RAKYAT MELAYU RIAU UNTUK MENINGKATKAN PEMAHAMAN MEMBACA SISWA - Nana Rahayu; Hasnah Faizah; M. Nur Mustafa; Elmustian; Hermandra (Jurnal PAJAR (Pendidikan dan Pengajaran), 2022)
This study addresses the low Japanese reading comprehension of students in the Japanese Language Education study program at FKIP, Universitas Riau. Interviews with students and lecturers revealed that the main obstacle was difficulty in understanding texts due to unfamiliar Japanese vocabulary. The research aimed to examine the effectiveness of comic media adapted from Riau Malay folklore to improve students’ reading comprehension in 2021. The study used a quantitative approach with a quasi-experimental design employing a pretest-posttest control group. The population consisted of 40 students enrolled in reading comprehension courses, with 20 students in the experimental class and 20 in the control class. The experimental class received three cycles of treatment using the comic media. Data were collected through reading comprehension tests, and analysis using an Independent Sample T-Test via SPSS version 25 yielded a significance value of 0.001, which is less than 0.05. This indicates that the Riau Malay folklore comic media effectively improved students’ Japanese reading comprehension.